The stone formation in the Memotherm urethral stent implantation area: Is it a rare complication? - Karaköse, Ayhan; Atesci, Yusuf Ziya; Aydogdu, Ozgu (Canadian Urological Association Journal, 2014)
Recurrent urethral stricture is one of the biggest problems in urology. Urethral stents as an alternative treatment to traditional methods has been used since 1985 in the treatment of urethral strictures. The stone formation in the Memotherm urethral stent implantation area is a rare complication. We report the case of a 67-year-old man who presented a stone in the Memotherm urethral stent implantation area after 6 years from the urethral stent surgery.